Formative Assessment in Virtual Education: A Mini Review (LACCEI, 2024)
Formative evaluation in virtual education plays a fundamental role in today's educational process, making it necessary to know its development and application due to unforeseen educational modality changes. This is the case in which the problem found is that it does not exist. a unique way of carrying out evaluations that allow for improving educational quality. Being the objective of this to find the different ways of carrying out the training of academic evaluation through the investigations published by other researchers. The method used is PRISMA, which consists of searching for relevant articles to answer the problem and answer the objectives, through the analysis of the summaries of each investigation. As a result, there are 29 articles belonging to Dialnet, Scielo, Redalyc, and Scopus, which allows for more information on formative evaluation, finding coincidences and central ideas that delve into the subject, likewise, the discussion between authors or researchers come to have something in common, it is necessary to say that formative evaluations are necessary through a process that allows students to develop knowledge and skills. It is concluded that the formative evaluation allows not only to assess of what has been learned but also the entire process followed It generates motivation in students because it strengthens their self-esteem and makes them persevere in the development of their proposed activities.